The Responsibilities of Social Work for Ecosocial Justice - Belén Parra Ramajo; Núria Prat Bau (Social Sciences)
The crisis of civilization we are experiencing unbalances the inter-relational, interdependency and intergenerational relationships of the planetary ecosystem, putting all species at risk. The current relationship between the unlimited economic development model and its social impacts in all regions, territories and communities is analyzed. These are more severe in the global South and the most impoverished populations, which often leads to conflicts, the deterioration of subsystems of life, and, as a result, movements of people. These challenges highlight the close interrelationship between social justice and issues of ecological injustice acting as a new source of inequality. The responsibility of social work, which is called on to incorporate the ecosocial perspective in all its areas and dimensions of practice, is becoming consolidated. To achieve this, five measures are proposed: expanding and strengthening the ethical and political basis of the profession; promoting the skilling-emancipatory models; cutting across all levels, methodologies and action areas; new fields of practice for ecosocial work; and introduction into social work curriculums. Social justice cannot be fully achieved without taking ecological justice into account.